2016
DOI: 10.1097/jsm.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Intolerance and Autonomic Dysfunction in Youth With Persistent Postconcussion Symptoms

Abstract: Our study is the first to prospectively characterize autonomic dysfunction in patients with persistent PCSs using HUT testing and to show that the tilt test abnormalities normalize in some patients as PCSs improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 32 publications
3
41
0
2
Order By: Relevance
“…Studies of autonomic dysfunction following mTBI have assessed heart rate variability, pupillary light reflex, arterial pulse wave, and graded exercise testing . One such study showed head‐upright tilt table abnormalities similar to postural orthostatic tachycardia syndrome (POTS) in youth with persistent post‐concussion syndrome . Another study showed a group of 8 patients who developed POTS based on head‐upright tilt table test after TBI .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of autonomic dysfunction following mTBI have assessed heart rate variability, pupillary light reflex, arterial pulse wave, and graded exercise testing . One such study showed head‐upright tilt table abnormalities similar to postural orthostatic tachycardia syndrome (POTS) in youth with persistent post‐concussion syndrome . Another study showed a group of 8 patients who developed POTS based on head‐upright tilt table test after TBI .…”
Section: Discussionmentioning
confidence: 99%
“…Investigations that deeply phenotype individuals with PTH and compare the PTH phenotype to migraine might lead to identification of features that are more representative of PTH compared to migraine. Based on our clinical observations and published literature demonstrating evidence for autonomic dysfunction following mild traumatic brain injury (mTBI) and in those with migraine, we hypothesized that PTH is often accompanied by autonomic symptoms such as orthostatic intolerance, and that symptoms of autonomic dysfunction are more severe among those with PTH compared to those with migraine …”
mentioning
confidence: 99%
“…Other approaches such as using a tilt table to identify autonomic dysfunction in patients with persistent post-traumatic vertigo and lightheadedness13 might be appropriate. However, in the clinical setting, the role for tilt table testing remains unclear and identification of aetiological factors such as autonomic dysfunction may be assessed using simpler measures such as heart-rate variability or orthostatic intolerance, although the evidence for these tests currently remains limited 60…”
Section: Summary and Recommendationsmentioning
confidence: 99%
“…Thus, asymptomatic athletes exhibited modifications in cardiac autonomic modulation weeks to months after concussion that became apparent only during physical exertion. A recent prospective study 51 of adolescents 13 to 18 years of age with PCS provides an idea of the prevalence of autonomic dysfunction after concussion: 70% of these patients had abnormal cardiac tilt-table results. Thus, symptomatic orthostatic intolerance may be a clinical physiological biomarker of concussion, one that can be assessed in the examination room or on the sideline.…”
Section: The Physiology Of Concussionmentioning
confidence: 99%